Running performance in middle-school runners - Malison, E. R.; Plank, D. M.; Brown, J. D.; Cheatham, C. C.; Mahon, A. D. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: This study examined the relationship of 3-km run time to indices of aerobic and anaerobic ability in 9 male runners (13.4+/-0.6 years, mean+/-SD). METHODS: Anthropometric measurements were made, and an exercise test to determine running economy at 187 m x min(-1) and (.-)VO(2max) were assessed on a treadmill. On a separate day, 2 55-m sprints followed by a 3-km run were performed on a 200-m indoor track. Capillary blood samples were obtained from a finger tip immediately after the run to determine blood lactate level. Fractional utilization (%(.-)VO(2max) used during the 3-km run) was calculated. Correlations were used to examine the relationship between run time and the physiological measurements. RESULTS: Mean values for (.-)VO(2), HR and RER at maximal exercise were 61.7+/-4.4 ml x kg(-1)xmin(-1), 198.9+/-6.7 b x min(-1), and 1.16+/-0.04, respectively. The average time to run 3 km was 13.27+/-0.97 min (90.1+/-7.2% of (.-)VO(2max)). Post-run blood lactate level was 8.3+/-3.2 mmol x L(-1) and was significantly related (r=-0.73, p=0.02) to 3-km time. Fractional utilization tended to be related (r=-0.56, p=0.12) to time. CONCLUSIONS: In this age group the ability to run at a high percentage of (.-)VO(2max) and tolerate a high blood lactate appear to be important determinants of running performance in young male runners.